2012
DOI: 10.1523/jneurosci.3079-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Evidence Consistent with Reduced Neuroplasticity in Human Adolescents Born Preterm

Abstract: Preterm-born children commonly experience motor, cognitive, and learning difficulties that may be accompanied by altered brain microstructure, connectivity, and neurochemistry. However, the mechanisms linking the altered neurophysiology with the behavioral outcomes are unknown. Here we provide the first physiological evidence that human adolescents born preterm at or before 37 weeks of completed gestation have a significantly reduced capacity for cortical neuroplasticity, the key overall mechanism underlying l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 43 publications
(2 reference statements)
2
33
0
2
Order By: Relevance
“…This relationship is most likely to be mediated by the stress hormone cortisol which has been shown to influence rTMS-induced plasticity (Clow et al 2014;Pitcher et al 2012;Sale et al 2008). While we did not directly measure cortisol, the relationship between cTBSinduced neuroplasticity and stress is consistent with animal studies showing that high corticosterone release facilitates LTD (Chaouloff et al 2008;Yang et al 2004), and one human study which similarly showed that higher levels of salivary cortisol are strongly associated with a greater response to cTBS (Pitcher et al 2012). The current finding shows that the perceived stress scale (Cohen et al 1983) is associated with cTBS-induced MEP suppression, and could be used to explain some of the variability in LTD-like rTMS-induced neuroplastic responses.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship is most likely to be mediated by the stress hormone cortisol which has been shown to influence rTMS-induced plasticity (Clow et al 2014;Pitcher et al 2012;Sale et al 2008). While we did not directly measure cortisol, the relationship between cTBSinduced neuroplasticity and stress is consistent with animal studies showing that high corticosterone release facilitates LTD (Chaouloff et al 2008;Yang et al 2004), and one human study which similarly showed that higher levels of salivary cortisol are strongly associated with a greater response to cTBS (Pitcher et al 2012). The current finding shows that the perceived stress scale (Cohen et al 1983) is associated with cTBS-induced MEP suppression, and could be used to explain some of the variability in LTD-like rTMS-induced neuroplastic responses.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] This disruption of brain development has important consequences for these children's long-term brain development, [26][27][28] including poorer school readiness skills. 29 Consequently, preterm children have fewer adaptive skills to help them learn in groups and maintain positive relationships with peers, [29][30][31] factors that will also influence the stability of EB problems at school entry.…”
Section: Discussionmentioning
confidence: 99%
“…Further, shortened gestation is associated with brain development even among children born full term (Davis et al, 2011). These structural abnormalities are accompanied by functional impairments in infancy and childhood, including working memory deficits (Beauchamp et al, 2008; Bhutta et al, 2002), resting state networks developed at different rates (Doria et al, 2010), reduced cortical plasticity for learning and memory (Pitcher et al, 2012), and absence of default mode network (Smyser et al, 2010). Several recent studies suggest that impairment of the brain’s capacity to integrate information between different regions may be a primary consequence of preterm birth (Ment et al, 2009; Scheinost et al, 2012; Woodward et al, 2005).…”
Section: Introductionmentioning
confidence: 99%